(untitled) (e-Journal of Linguistics, 2024)
This paper examines the linguistic meaning of language in memes and jokes on the internet, focusing on the dynamic nature of online platforms like Reddit. It aims to understand the language distinctions underlying humor found in these platforms, which often defy accepted linguistic conventions. Implicit meaning, derived from the verb "to imply," refers to something that a speech implies but does not state outright. In conversational encounters, the idea of cooperation between speakers is inextricably linked to the understanding of implicature. The paper highlights the importance of understanding the linguistic features of jokes and memes on the internet, as they become a breeding ground for linguistic innovation. The meaning of a sentence can be divided into conventional meaning, conversational implicatures, and conventional implicatures. Internet memes and jokes, often used for propaganda, satire, and defamation, can contain implicatures. The study examined internet-published memes and jokes involving implicatures and aimed to identify other joke styles and implicatures. Gender-related implicatures are common in jokes, with conventional implicature being the most common. Examples include jokes about women, cultural basic jokes, and social phenomena. The analysis of implicatures in jokes involves evaluating extrinsic linguistic factors, including social and cultural dimensions, and the influence of context on the inferred meaning. Overall, the interpretation of internet memes and jokes is influenced by their linguistic features.